Spatiotemporal variability of turbulent fluxes in snow-covered mountain terrain - Engbers, Rainette; Gonzàlez-Herrero, Sergi; Gerber, Franziska; Wever, Nander; Lehning, Michael (Frontiers in Earth Science, 2025)
Turbulent exchange of heat and moisture plays an important role in snow cover dynamics. Although these processes are subject to great spatial and temporal variability, especially in complex terrain, measurements of heat, moisture, and momentum fluxes are almost exclusively point observations. Numerical modeling offers a means to assess the spatial variability of fluxes and evaluate the representativeness of point observations. This study addresses this challenge by examining the spatiotemporal variability of surface–atmosphere energy exchange during different meteorological events in the Swiss Alps using the NWP model CRYOWRF. We analyze sources of errors in representing energy exchange over snow in mountain areas by models. To investigate this, we first compared fluxes derived from Monin-Obukhov parameterizations with direct Eddy Covariance measurements. While the parameterization generally captures the sign of the fluxes, it tends to underestimate their magnitude, up to 20 W m−2 for latent heat flux. We then evaluate CRYOWRF—the WRF model coupled with the SNOWPACK land-surface scheme–in representing fluxes and mean quantities. Simulations at 1 km and 200 m resolution are compared against data from 21 meteorological stations in a 40 × 40 km domain in the Swiss Alps during three conditions: a South Föhn, a North Föhn, and a quiescent day. Our findings indicate that while higher-resolution simulations improve agreement between measured and modeled variables, they tend to underestimate wind speeds (with a bias of up to 1.5 ± 0.2 m s−1), and turbulent fluxes (up to 14 ± 3.7 W m−2) and consequently lower snow surface temperatures (up to 3.3 ± 0.3 °C). In contrast, coarser-resolution simulations overestimate wind speeds, and therefore, heat fluxes. Our research demonstrates that magnitudes of turbulent fluxes scale linearly with local wind speeds (r-values between −0.80 and −0.98 for sensible heat flux on a south föhn day, p-values < 0.001), with locations at similar elevations exhibiting comparable trends of increasing turbulent flux with wind speed. Although temperature and humidity gradients generally decrease with elevation, higher elevations still experience greater net energy exchange between the surface and the atmosphere. A net magnitude increase of 30 W m−2 is observed between elevation differences of 1,000 m. Overall, our results suggest that point measurements should be used with caution for representing broader terrain conditions, especially when extrapolated for different elevations.